Use of propolis and ε-polylysine as preservative agents in beaten yogurt - Lectong-Cusme, Nieve Esther; López-Pinargote, Isaac Leonel; Parrales-Mendoza, Vicky Yuliana; Quiñonez-Becerra, Neiva Marcela; Bravo-Zamora, Beatriz María; Cevallos-Mendoza, Arnaldo Narcizo (Revista Colombiana de Investigaciones Agroindustriales, 2022)
This work studied alternatives to replace conventional preservatives used in the food industry. The objective of this research was to evaluate the effect of the mixture of propolis and ε-polylysine, through statistical analysis, to identify variations in yogurt stability, microbial development, changes in physicochemical properties, shelf life, sensory acceptability and determine the better concentrations of preservatives. Five treatments (T1: 5 mg ε-polylysine – 1 mL Propóleo, T2: 10 mg de ε-polylysine – 0,9 mL de propóleo, T3: 15 mg de ε-polylysine – 0,8 mL de propóleo, T4: 20 mg de ε-polylysine – 0,7 mL de propóleo, y T5: 25 mg de ε-polylysine – 0,6 mL de propóleo) were carried out with a mixture of propolis and ε-polylysine in a completely randomized design with 3 replications. The properties of the preservative in the mixture were analyzed in terms of pH, acidity, count of Staphylococcus aureus, Escherichia coli, molds and yeasts in yogurt stored for 30 days at 4 °C. Significant reduction in pH due to preservatives was observed: T4 - T5 values ​​(4,69; 4,63) higher than T3 - T1 - T2 values ​​(4,39; 4,24; 4,39) are considered more suitable for international standards. In the samples analyzed there was no evidence of the presence of S. aureus, and E. coli. The stability of the product was calculated using the amount of molds and yeasts as an indicator according to the Labuza equation. The sensory analysis was carried out with 75 participants without training, which indicated that the treatment T2 and T3 have the highest overall acceptability.